Evaluasi Pelaksanaan Peraturan Daerah Nomor 18 Tahun 2011 Tentang Keterbukaan Informasi Publik dalam Penyelenggaraan Pemerintah Kota Padang - Annisya Septria Yunika; M. Fachri Adnan (Policy, Law and Political Research Center, 2026)
This study examines the implementation of Regional Regulation Number 18 of 2011 concerning Public Information Disclosure in the Padang City Government. The study used a descriptive qualitative method with William N. Dunn’s policy evaluation theory. Data were collected through interviews, observations, and documentation. The findings indicate that public information services in Padang City have been implemented through PPID, although several obstacles remain, including limited human resources, uneven access to information, and less optimal use of digital technology. This study recommends improving human resource capacity, strengthening digital information services, and increasing public awareness regarding access to public information.